Reliability and usefulness of the 30-15 intermittent fitness test in male and female professional futsal players - Valladares-Rodriguez, S.; Rey, E.; Mecias-Calvo, M.; Barcala-Furelos, R.; Bores-Cerezal, A. J. (Journal of Human Kinetics, 2017)
The purpose of this study was to determine the reliability and usefulness of the 30-15 Intermittent Fitness Test (30-15IFT) in professional male and female futsal players. Thirteen male (24.4 ± 5.6 years; 174.5 ± 10.3 cm; 70.3 ± 9.9 kg) and fourteen female (23.3 ± 4.5 years; 165.8 ± 6.2 cm; 61.7 ± 5.5 kg) professional futsal players performed the 30-15IFT on two occasions, separated by 5 days. Maximal intermittent running velocity (VIFT) and heart rate at exhaustion (HRpeak) data were collected for both tests. Reliability was assessed by the intraclass correlation coefficient (ICC), typical error (TE) expressed as a coefficient of variation (CV), and smallest worthwhile change (SWC). VIFT demonstrated very good reliability between sessions, both for male (ICC = 0.92) and female (ICC = 0.96) players. As the TE for VIFT and HRpeak was similar to the calculated SWC for both male and female players, the usefulness of the test was rated as "medium". A change in performance of at least 2 stages in male players, or a change of more than 1 stage in female players could be interpreted as a meaningful change in aerobic futsal fitness. The results of this study demonstrate that the 30-15IFT is both a reliable and useful test for male and female professional futsal players.